Voltaire with Nietzsche: The Problem of the Object in Psychology - Andrade Rodríguez, Ricardo Alberto (Poiésis, 2009)
One question, for some a candid question, is positioned in the atmosphere of academic psychology, in fact, I dare say, all the programs in psychology, at least, they ought to be: what does psychology study? Immediate responses can come from many sectors, some with a pompous title of "more scientific", other than, with some suspicion scratch, for some, discredited in the categories of "pseudoscience" or, in a less dramatic way, "ideologies".